COMMONALITIES AND DIFFERENCES IN THE TEXT OF THE AUTHOR'S SPEECH IN THE STORY “O‘TMISHDAN ERTAKLAR” (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article talks about the discrepancies in the different editions of this work of some of the words used in the author's speech in The Story “Tales from the past” by Abdullah Qahhor. Literary language and adib speech are studied using the method of comparative analysis.